THE COMPOSITION OF HAND LINE CATCHS IN THE AFTERNOON AND NIGHT IN TANJUNG MUTIARA SUB DISTRICT, AGAM REGENCY, WEST SUMATERA PROVINCE - Bima Guntara; Arthur Brown; Polaris Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe study was conducted on July 2017 in Tanjung Mutiara sub-district, Agam regency, West Sumatera Province. This study aims to analyze the composition of catches, determine the type and number of catches during afternoon and night on fishing equipment hand line. The method used in this study is a participative and research conducted during 20 days of arrest. The catch during the study was 3690.42 kg (15454 fishes). The results of the research composition of hand line shot during afternoon is 825.17 kg (3624 fishes), while at night 2865,25 kg (11830 fishes). The catch consists of eleven species. The night catches bigger than the afternoon catch. Keywords: Hand line, Composition Catch Fish, Afternoon and Night Period, Tanjung Mutiara